Tolerance in a multicultural society as a reflection of pancasila values - Risladiba, Risladiba (Universitas Tanjungpura, 2025)
The reality of Indonesia's heterogeneous society, including ethnicity, culture, race, religion, beliefs, and various other determinant factors, has become an opening to trigger horizontal conflicts in society. Efforts to understand this reality are not only through discourse, but in the form of implementing tolerant attitudes and behaviors in line with the content of the values in Pancasila. This study aims to analyze the various forms of tolerance carried out by the Dayak Losarang community, both towards their fellow members and with the surrounding community. The research method used to examine the issue uses a qualitative method through a case study approach. Data collection was carried out by involving participants from the Dayak Losarang community. The results showed that tolerance as contained in the values of Pancasila can bind the components of heterogeneity in the life of this very pluralistic Indonesian society. The existence of an attitude of tolerance that is realized in the life of the Losarang Dayak community can maintain harmony in the community environment. So that with a variety of different traditions such as the kidung alas turi ritual and praise of nature, as well as different beliefs can be accepted by the surrounding environment without causing conflict that leads to division. The existence of understanding and awareness of tolerance, in addition to referring to the value of Pancasila, also arises from the belief in the natural history of ngaji rasa that they are.